The nature of the beast [compact disc, unabridged] - Penny, Louise (Penny, Louise. Three Pines mystery., 2015)
Hardly a day goes by when nine year old Laurent Lepage doesn't cry wolf. From alien invasions, to walking trees, to winged beasts in the woods, to dinosaurs spotted in the village of Three Pines, his tales are so extraordinary no one can possibly believe him. Including Armand and Reine-Marie Gamache, who now live in the little Quebec village. But when the boy disappears, the villagers are faced with the possibility that one of his tall tales might have been true.